Saudi Arabia : Financial System Stability Assessment, including Reports on the Observance of Standards and Codes on the following topics, Monetary and Financial Policy Transparency, Banking Supervision, and Payment Systems. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
The capacity of the Saudi Arabian banking sector to respond to macroeconomic shocks has been considerably strengthened over the past decade. The Saudi Arabian Monetary Agency (SAMA ) has been actively monitoring some emerging portfolio trends. Comprehensive reforms are under way to deepen financial markets and increase access to financial services. Resolving structural issues remains an obstacle for the market development. SAMA adheres to the Basel Committee's Core Principles for Effective Banking Supervision, and it makes no differentiation between conventional and Sharia-compliant banking arrangements.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet